(untitled) (The Research of Medical Science Review, 2025)
Background: Organ transplantation represents a major advancement in medical science, offering patients with end-stage organ failure a renewed chance at life. Among these, kidney and liver transplants are the most frequently performed procedures worldwide. While medical and surgical advancements have significantly improved survival outcomes, the long-term effects of transplantation on patients' quality of life (QoL), mental health, and well-being remain a significant concern. Recipients face challenges such as lifelong immunosuppressive therapy, risk of complications, financial strain, and psychological adaptation—all of which affect their daily functioning and mental state. Objectives: This study aimed to assess and compare the quality of life, mental health, and overall well-being of patients who have undergone kidney or liver transplantation. Methods: A comparative cross-sectional study was conducted at the Pakistan Kidney and Liver Institute and Research Center (PKLI&RC), Lahore, Pakistan. The study included 130 adult transplant recipients (65 kidney and 65 liver), who had undergone surgery at least six months before data collection and were clinically stable. A purposive sampling technique was employed. Data were collected using three validated tools: the Short Form Health Survey (SF-36), the Hospital Anxiety and Depression Scale (HADS), and the WHO-5 Well-Being Index. Descriptive statistics, t-tests, and 95% confidence intervals were used to assess and compare psychological and quality of life indicators between the two groups. Results: The mean age of the participants was 44.4 ± 11.0 years, with a male predominance (66.9%). Anxiety and depression levels were significantly higher in liver transplant recipients (mean anxiety score: 8.10 ± 4.00, mean depression score: 8.00 ± 4.50) than kidney recipients (anxiety: 6.90 ± 3.20, depression: 6.50 ± 4.10), with statistically significant differences (p = 0.038 and p = 0.027, respectively). Although the mean WHO-5 well-being score was higher in kidney recipients (15.23 ± 5.89) than liver recipients (13.62 ± 6.48), the difference was not statistically significant (p = 0.139). However, significant differences were observed across all eight SF-36 quality of life domains, including physical functioning, bodily pain, general health, social functioning, and mental health, with kidney transplant recipients consistently reporting better scores than liver recipients. Conclusion: While both kidney and liver transplants greatly improve patient survival, kidney transplant recipients reported significantly better quality of life and mental health outcomes than liver transplant recipients. Liver transplant patients experienced higher levels of anxiety and depression, underscoring the need for integrated mental health and psychosocial support in post-transplant care.